Pendampingan Penyusunan AKNOP dan Kinerja Embung Balai Besar Kabupaten Blitar, Tulungagung, dan Malang: Pendampingan Penyusunan AKNOP dan Kinerja Embung Balai Besar - Rina Sri Wulandari; Luqman Hakim; Medya Ayunda Fitri (Journal of Science and Social Development, 2021)
The Technical Audit is carried out to find out all the conditions andfunctions of the raw water sources in the BBWS Brantas Work Area from theTechnical Audit activities to have output reports that can be used by decision-makers to determine which ponds to maintain, including from a technical and costperspective. The legal basis used to follow up on these activities is contained in LawNo. 11 of 1974 concerning Irrigation as stated in the general explanation and Article12 regarding maintenance, besides that it is also contained in GovernmentRegulation No. 37 of 2010 concerning dams. So that BBWS Brantas as an extensionof the Central Government needs to carry out Technical Audit activities and thepreparation of AKNOP for Reservoirs in the Blitar, Tulungagung, and MalangRegions. The aims and objectives of carrying out the Technical Audit and thepreparation of the AKNOP of the Madura area dams are the availability of raw waterinventory data for the Blitar, Tulungagung, and Malang areas in the BBWS Brantaswork area, the availability of technical data, conditions and functions of thereservoirs for the Blitar, Tulungagung and Malang areas so that it can become atechnical reference in planning Operations and Maintenance in the future.Technically, the damage that generally occurs to raw water facilities andinfrastructure that is built is caused by a lack of maintenance carried out by thecaretaker of the raw water location.